2005
DOI: 10.1001/archopht.123.9.1231
|View full text |Cite
|
Sign up to set email alerts
|

Cataract and Barriers to Cataract Surgery in a US Hispanic Population

Abstract: To report the prevalence of visually significant cataract and cataract surgery and to determine demographic and socioeconomic factors that influence use of cataract surgery in a US Hispanic population. Methods: Proyecto VER is a population-based study of Hispanic individuals, 40 years or older, living in southern Arizona. Visual acuity was measured monocularly, and a dilated ophthalmic examination was performed to determine lens opacities. Visually significant cataract was defined as severe levels of opacity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
68
3
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 19 publications
2
68
3
1
Order By: Relevance
“…Previous studies have provided population-based estimates of the prevalence of cataract surgery in U.S. population groups. 1,[13][14][15][16] However, populationbased estimates of the incidence of cataract surgery in the U.S. are limited. [2][3][4] The Beaver Dam Study, 4 which is similar to the REP in location and sociodemographics, reported a 6.3% cumulative cataract surgery incident rate in persons 43 years and older during a 4.8-year study period.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have provided population-based estimates of the prevalence of cataract surgery in U.S. population groups. 1,[13][14][15][16] However, populationbased estimates of the incidence of cataract surgery in the U.S. are limited. [2][3][4] The Beaver Dam Study, 4 which is similar to the REP in location and sociodemographics, reported a 6.3% cumulative cataract surgery incident rate in persons 43 years and older during a 4.8-year study period.…”
Section: Discussionmentioning
confidence: 99%
“…It has been repeatedly shown that, even when surgical services are made available, the proportion of the population willing to take up such services often remains modest 5 6. A number of studies in Asia,5 7 – 10 Africa1113 and elsewhere14 have pinpointed barriers to cataract surgical care, including cost,5 8 – 12 lack of knowledge,8 – 11 15 16 fear of pain or poor outcomes,5 9 11 and various “attitudinal” barriers,5 9 such as acceptance of poor vision among women or the old.…”
mentioning
confidence: 99%
“…Whereas studies of barriers to uptake of cataract services are comparatively plentiful, relatively few studies14 have focused on subjects who have successfully accessed services in relatively under-served areas, in order to assess how they overcame impediments of knowledge or cost.…”
mentioning
confidence: 99%
“…The three categories of nuclear sclerosis, cortical, and posterior subcapsular were not exclusive of each other. In the Proyecto VER study of Mexican participants in Arizona 40 years old and older, 2.8% of 4774 participants were reported to have visually-significant cataracts (Broman, Hafiz, Munoz, Rodriguez, Snyder, Klein and West, 2005). Emanuelli et al (2005) reported a prevalence of lens opacities in 22.1% of the charts surveyed of their Puerto Rican patients.…”
Section: Prevalence Of Systemic and Ocular Disease By Birth Countrymentioning
confidence: 99%